Exploring the Future of Remote User Research - Martelaro, Nikolas (2020)
ABSTRACT The rapid move to remote work due to COVID-19 social distancing policies has slowed or stopped most in-person qualitative user research activities. The limitation on in-person activities has pushed many user researchers to consider how they can continue their research remotely and presents an opportunity for user research teams to (re)design their research processes for remote work. In this position statement, I outline prior work in remote qualitative user research methods and discuss how this work can help us to (re)design new tools, methods, and frameworks that can enable remote work. I then propose a set of research questions that can further our knowledge and abilities to conduct effective remote user research. With creative development, we can create remote research methods that afford new ways of understanding user experience today and build more environmentally conscious and accessible research practices for a future where remote research is much more common. ABOUT THE AUTHOR/S Nikolas Martelaro Carnegie-Mellon University nikmart@cmu.edu Nikolas Martelaro (nikmartelaro.com) is an Assistant Professor in the Human-Computer Interaction Institute at Carnegie Mellon University. My lab focuses on augmenting designer's capabilities through the use of new technology and design methods. My interest in developing new ways to support designers stems from my interest in creating interactive and intelligent products. I graduated from Stanford University's Center for Design Research where I was advised by Larry Leifer and Wendy Ju. New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).